PEMAHAMAN DAN PERSEPSI ANGGOTA DPRD KOTA SURAKARTA TERHADAP PENYAJIAN LAPORAN KEUANGAN SEKTOR PUBIK - Fadjar Harimurti, Ika Listyawati, Bambang Widarno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
This study aimed to analyze the level of understanding of Surakarta City Council Members To The Financial Statements and the Public Sector Perceptions Surakarta City Council Member of the Financial Statements on education. This study is a survey of the population of Surakarta City Council Member 2014 - 2019 Forces with sampling techniques census method used in this study, namely all the population sampled in this study, so that the sample in this study amounted to 45 samples can be processed but which amounted to 41 samples. The technique of collecting data using questionnaires. The method of analysis used descriptive analysis, to collect, process, and interpret data. The results showed that Assembly Members Surakarta not understand the financial statements of public sector and the perception of Surakarta City Council Member to the presentation of financial statements of public sector agreed to presentation of financial statements conducted by SKPD Surakarta.Keywords: understanding financial statements, public sector, financial reports.